Acceptability and feasibility of a task-shifted collaborative care model for depression and anxiety in primary HIV clinics in the Philippines: a qualitative inquiry - Anna Maureen Dungca-Lorilla; Jennifer Mootz; Maria Isabel Melgar; Roxanne Emily Tanuecoz; Timothy John Dizon; Annette H. Sohn; Rossana Ditangco (BMC Health Services Research)
Abstract Background Depression and anxiety can greatly impact the overall health of a person living with HIV (PLHIV). Management of mental health disorder should be an integral part of HIV care. The Collaborative Care Model (CoCM) is an evidence-based model of care that integrates mental health in primary care. This study aimed to assess the acceptability and feasibility of implementing the CoCM for depression and anxiety in HIV clinics in the Philippines using HIV counsellors as care managers. Methods We conducted a descriptive qualitative study by facilitating focus group discussions (n = 7) and key informant interviews (n = 18) with 53 HIV and mental health stakeholders, including PLHIV (n = 20), HIV counsellors (n = 11), physicians (n = 10), clinic heads (n = 4), policy makers (n = 4), and mental health providers (n = 4) from August 2021 to March 2022. Participants were recruited from 17 HIV clinics in the Philippines. We employed a thematic analysis using the Consolidated Framework for Implementation Research (CFIR) domains as themes. Results Almost all PLHIV participants were men (95%), with a mean age of 28 years. The other stakeholders had a mean age of 44 and had worked in their field for an average of 8 years. Overall, 58% were women. Factors that influenced the acceptability of the CoCM included the possibility of increased access to mental health services with a more holistic care team. Perceived barriers included inadequate numbers of psychiatrists, an overburdened and understaffed HIV workforce, low mental health knowledge among HIV providers, and implementation cost. Perceived facilitators were willingness of HIV providers to provide care and knowledge of HIV counselling. Conclusion We found the CoCM to be acceptable among study participants. Recommendations included capacity building for HIV providers, collaborations within and across clinics to facilitate access to psychiatrists, clear management protocols, and pilot testing. Mental health and HIV care coverage within national policies should be amended to allow for non-mental health specialists to provide low-intensity therapies. Closer partnerships among HIV and mental health policy makers would improve integration implementation.